Method of Finding the Cube Root of Any Perfect Cube Number or Quantity - Verma, Manohar Lal (SCHOOL SCIENCE, 2015)
We can find cube root of any perfect cube number with the method given below. We know that: (a+b)3 = a3 + 3ab (a+b)+b3 The value of b3 is equal to the cube of ones digit of the given quantity or number.